Projek program perumahan masyarakat setempat - Mohamed @ Ismail, Ab. Rahman (2016)
The aim of this research is to (i) review the effectiveness of the implementation of PPMS. PPRT is a program contained in the Seventh Malaysia Plan (1996-2000) for the repair of houses Malaysia underprivileged in rural areas. One of the programs contained in the PPRT is PPMS. This program provides financial assistance for the development and management of settlement areas targeted groups either in-situ or new settlements. This project is to help increase the income of the supply needs of social facilities such as community halls, surau and others for their use. In addition, this project will also help to provide infrastructure and basic utilities such as electricity and water supply connection and perform repair work on existing infrastructure. The location chosen was in PPMS Project Sg. Gersik, Muar. It starts with a visit to the Secretariat of the Focus Group which was held on 15 November 2015 to study and found that the house and the infrastructure is in unsatisfactory level. In this study, primary data obtained from interviews face to face with the PPMS Project Sg. Gersik, Muar, while secondary data collected from government reports. The data were analyzed qualitatively presented in the description and explanation. Some suggestions were made such as establishing an agreement to occupy the house in PPMS and feasibility study of the new resettlement area and increase the area of land through the PPMS Project Land Acquisition (PBT) by the government. Finally, any agreement made by the participants and the government met to ensure project management PPMS at its best.